The effect of high intraocular pressure on enzymatic antioxidant system of uveal tissues in rabbits with experimental allergic uveitis (Ukrainian Journal of Ophthalmology, 2025)
Background. Determining the influential mechanisms of high intraocular pressure on the development and course of non-infectious anterior uveitis is a relevant but understudied issue which requires a detailed study. Of particular interest, in this regard, are free radical mechanisms which can be a trigger for oxidative stress and cause damage to cell membranes in ocular tissues. Purpose. To study the activity of antioxidant enzymes (glutathione peroxidase, superoxide dismutase, and catalase) in uveal tissues and chamber aqueous humor in rabbits with experimental non-infectious anterior uveitis with and without ocular hypertension. Material and Methods. The experiment involved forty-one animals divided into 4 study groups: Group 1 (n = 10), ocular hypertension (OH); Group 2 (n = 10), uveitis (U); Group 3 (n = 12), (OH+U); Group 4 (n = 9), intact animals as control. Allergic uveitis was simulated using our method through the administration of bull serum albumin with a dose of 5 mg in previously sensibilized animals. To simulate ocular hypertension in the experimental groups 1 and 3, the animals were made a single 0.1 ml injection of 0.3% carbomer in the anterior chamber. Biochemical studies were conducted spectrophotometrically for the tissues of the uvea (the iris and the ciliary body) and the aqueous humour. The activity of antioxidant enzymes (glutathione peroxidase, superoxide dismutase, and catalase) was determined. Parametric statistical tests with Student's t-test using the Statistica package were used to process the data.Results. Ocular hypertension in experimental non-infectious anterior uveitis resulted in a more intensive decrease in the activity of the enzymatic antioxidant system (by 19.4 and 20.9% for superoxide dismutase; by 25.5 and 21.9% for glutathione peroxidase; and by 14.3 and 19.6% for catalase) in the aqueous humor and uveal tissues, respectively, compared to the rabbits with uveitis and normal intraocular pressure. Conclusions. A decrease revealed in the activity of superoxide dismutase, catalase, and, especially, glutathione peroxidase testifies to depletion of the enzymatic antioxidant system in experimental conditions of increased peroxidation in the uveal tissues in ocular hypertension. Our findings confirm the assumption that elevated intraocular pressure can be a factor contributing to severe inflammation in the anterior eye. One of the major cell mechanisms inducing such pathological conditions is oxidative stress.
Keywords: ocular hypertension; uveitis; glutathione peroxidase; superoxide dismutase; catalase; rabbits